Is There a Crucial Link Between Vitamin D Status and Inflammatory Response in Patients With COVID-19? - Saponaro, Federica; Franzini, Maria; Okoye, Chukwuma; Antognoli, Rachele; Campi, Beatrice; Scalese, Marco; Neri, Tommaso; Carrozzi, Laura; Monzani, Fabio; Zucchi, Riccardo; Celi, Alessandro; Paolicchi, Aldo; et al. (Frontiers in Immunology, 2022)
Background Hypovitaminosis D has been suggested to play a possible role in coronavirus disease 2019 (COVID-19) infection. Methods The aim of this study is to analyze the relationship between vitamin D status and a biochemical panel of inflammatory markers in a cohort of patients with COVID-19. A secondary endpoint was to evaluate the correlation between 25OHD levels and the severity of the disease. Ninety-three consecutive patients with COVID-19-related pneumonia were evaluated from March to May 2020 in two hospital units in Pisa, in whom biochemical inflammatory markers, 25OHD levels, P/F ratio at nadir during hospitalization, and complete clinical data were available. Results Sixty-five percent of patients presented hypovitaminosis D (25OHD ≤ 20 ng/ml) and showed significantly higher IL-6 [20.8 (10.9–45.6) vs. 12.9 (8.7–21.1) pg/ml, p = 0.02], CRP [10.7 (4.2–19.2) vs. 5.9 (1.6–8.1) mg/dl, p = 0.003], TNF-α [8.9 (6.0–14.8) vs. 4.4 (1.5–10.6) pg/ml, p = 0.01], D-dimer [0.53 (0.25–0.72) vs. 0.22 (0.17–0.35) mg/l, p = 0.002], and IL-10 [3.7 (1.8–6.9) vs. 2.3 (0.5–5.8) pg/ml, p = 0.03]. A significant inverse correlation was found between 25OHD and all these markers, even adjusted for age and sex. Hypovitaminosis D was prevalent in patients with severe ARDS, compared with the other groups (75% vs. 68% vs. 55%, p < 0.001), and 25OHD levels were lower in non-survivor patients. Conclusions The relationship between 25OHD levels and inflammatory markers suggests that vitamin D status needs to be taken into account in the management of these patients. If vitamin D is a marker of poor prognosis or a possible risk factor with beneficial effects from supplementation, this still needs to be elucidated.